Effect of physical exercise on psychophysiological indexes of medical social workers - Fang Yin, Zhanchun Feng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study examines the impact of physical exercise on the mental health status of medical social workers in China. This research employs a questionnaire to investigate the mental and physical fitness of 200 medical personnel in China and assesses their mental health and degree of physical fitness. The questionnaire's reliability was evaluated by selecting sixty medical personnel from the species. The data were handled with SPSS11.5 statistical software, including Pearson's product-difference correlation analysis and variance ANOVA, among other analyses. The effective percentage of recovery for the questionnaire is 97%. Fewer individuals engage in exercise and have the goal to exercise, the greater the prevalence of stress. Medical social workers' experience of stress is inversely connected with their willingness and engagement in physical activity. The mental health status of medical social workers is strongly correlated with their athletic participation. The mental health status of medical social workers who regularly engage in physical activity is significantly superior to that of those who do not engage in physical activity or who rarely engage in physical activity. The introduction of medical social work provides a foundation for advancing the transformation of the medical model, the growth of medicine as a whole, and the government's efforts to improve the architecture of the medical and health service system.